Effect of Convergent Angle on the Fluid Dynamic of Fire-Fighting Nozzle - Riawan, Awinda Sari (METAL: Jurnal Sistem Mekanik dan Termal, 2025)
The nozzle is extensively used in many industrial contexts with variable shapes to satisfy particular application requirements, influencing fluid properties. Firefighting sprinkler nozzles have a variety of shapes, leading to research on the possibility of flow treatment devices to improve nozzle performance using numerical analysis. This simulation study examined three different geometry angles of the nozzle (15, 20, and 25 degrees) with different parameters (inlet pressure) and found that the optimal geometry performed the best in terms of pressure retention and velocity output, which are critical for efficient fire suppression operations, with performance varying significantly depending on nozzle angle and applied pressure. A nozzle with a 20-degree angle geometry showed the best performance, with good pressure retention and velocity output, both of which are important for efficient fire suppression. Developing a highly efficient and high-performing nozzle is critical for increasing efficiency and effectiveness in firefighting operations.